Involvement of heat shock proteins on Mn-induced toxicity in Caenorhabditis elegans. Issue 1 (December 2016) - Avila, Daiana; Benedetto, Alexandre; Au, Catherine; Bornhorst, Julia; Aschner, Michael
Abstract Background All living cells display a rapid molecular response to adverse environmental conditions, and the heat shock protein family reflects one such example. Hence, failing to activate heat shock proteins can impair the cellular response. In the present study, we evaluated whether the loss of different isoforms of heat shock protein (hsp ) genes inCaenorhabditis elegans would affect their vulnerability to Manganese (Mn) toxicity. Methods We exposed wild type and selectedhsp mutant worms to Mn (30 min) and next evaluated further the most susceptible strains. We analyzed survival, protein carbonylation (as a marker of oxidative stress) and Parkinson's disease related gene expression immediately after Mn exposure. Lastly, we observed dopaminergic neurons in wild type worms and inhsp-70 mutants following Mn treatment. Analysis of the data was performed by one-way or two way ANOVA, depending on the case, followed by post-hoc Bonferroni test if the overallp value was less than 0.05. Results We verified that the loss ofhsp-70, hsp-3 and chn-1 increased the vulnerability to Mn, as exposed mutant worms showed lower survival rate and increased protein oxidation. The importance ofhsp-70 against Mn toxicity was then corroborated in dopaminergic neurons, where Mn neurotoxicity was aggravated. The lack ofhsp-70 also blocked the transcriptional upregulation ofpink1, a gene that has been linked to Parkinson's disease. Conclusions Taken together, our data suggest that Mn exposure modulates heat shock protein expression, particularly HSP-70, inC. elegans . Furthermore, loss ofhsp-70 increases protein oxidation and dopaminergic neuronal degeneration following manganese exposure, which is associated with the inhibition ofpink1 increased expression, thus potentially exacerbating the vulnerability to this metal.